Perenniporia subrhizomorpha sp. nov. (Polyporales, Basidiomycota) from North China - Tian, Xue-Mei; Liu, Shi-Liang; Zhou, Lin-Jiang; Wang, Xue-Wei; Zhou, Li-Wei (Phytotaxa, 2021)
Perenniporia subrhizomorpha is introduced as a new species from North China on the basis of morphological and molecular evidence. Phylogenetically, based on ITS and nLSU regions, P. subrhizomorpha nested with two species belong to Perenniporia s.s. as a distinct lineage. Perenniporia subrhizomorpha is characterized by having an annual habit, resupinate and papery basidiomes, a dimitic hyphal system with crystal-covered generative hyphae in context, ellipsoid, truncated, dextrinoid basidiospores (5.7–6.5 × 4.3–5.5 μm), and absence of cystidia and cystidioles. Morphologically similar and phylogenetically related species to the new species are discussed.